Possible hidden cause of human immunodeficiency virus type 1 latency and role of interferon - Ahmed, Nursarat; Miura, Kazuki (Mediscope, 2016)
Latent human immunodeficiency virus type 1 (HIV-1) infected cells under antiretroviral therapy are reported to be resting memory CD4+ T cells; however, the mechanisms of HIV-1 latency is unclear. We demonstrate that long-term culture of interleukin-2-dependent CD4+ T cells with a memory phenotype mimicked latently HIV-1-infected cells in the presence of interferon-?. These cells are mostly resting and contained HIV-1 proviruses that could be re-activated by stimulation. Our findings suggest a potential role of type-1 interferon in HIV-1 latency. Mediscope Vol. 3, No. 2: July 2016, Pages 11-17